Analyzing Factors Attributing To Effectiveness of Performance Management System of a Manufacturing Industry - Panda, Sitansu; M., Waris; Khan, Asadullah; Ullah, Mehfooz; Adeleke, A. Q. (Academic Research Publishing Group, 2018)
Performance Management System (PMS) is considered as one of the vital aspects of Human Resource Management. PMS is the focus of study in this paper. The effectiveness of Performance Management System of a manufacturing company in Malaysia has been studied. And for this study, factor analysis is conducted. Different factors attributing to effectiveness of Performance Management System have been extracted and the study highlighted that Reward and Development, Continuous Communication and Departmental Development, Standard and Goal Setting, Developing HR Systems, Policy and Tool for Performance Management, Performance Measurement, Performance Linkage to Payment Decisions, Fairness for Employee Appraisal, Implementation and Employee Control, and Performance Review and Employee Recognition are the factors responsible for PMS Effectiveness. It has been suggested for taking developmental measures to enhance the existing Performance Management System contributing more for the benefits of organization and also for the betterment of the employees of the organization. Firstly, the importance of Performance Management System and the factors attributing to its effectiveness have been discussed in the introduction section. Secondly, relevant literature is being reviewed. It is followed by discussion about the methodology adopted in this study. Fourthly, results pertaining to this study and their analysis have been discussed in detail. Finally, concluding comments have been mentioned.